Pengaruh Penambahan Steel Fibre Terhadap Sifat Mekanis Beton Normal - Fachrurrozi Yusyaf; Alex Kurniawandy; Ermiyati Ermiyati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Many technology innovations have been created to meet development needed. A lot of research have conducted to find solution to improve the deficiency of concrete. The addition of fiber was an alternative to improve the mechanical properties of normal concrete. In this research, the concrete will be mixed with steel fiber and the examination of the mechanical properties are compressive strength, split tensile strength, and flexural strength. The length of steel fiber was 140 mm which the content variation were 0.2%, 0.4%, 0.6%, 0.8%, and 1% of the weight aggregate volume. The results showed that the compressive strength, the split tensile strength and the flexural strength have the highest value at 0.6%. Therefore, the addition of steel fibers into the concrete mix can improve the mechanical properties of concrete.Keyword : steel fiber, fiber-reinforced concrete, compressive strength, splitting tensile strength, flexural strength